Helping children resolve conflict in communication - Abd Rahim, Normaliza; Sujud, Arba'ie; Subramaniam, Vijayaletchumy; Nik Affendi, Nik Rafidah; Zainon Hamzah, Zaitul Azma (The International Journal of Learning, 2008)
Negotiation is something that we do all the time. Negotiation is usually considered as a compromise to settle an argument or issue to benefit ourselves as much as possible. Communication is always the link that will be used to negotiate the problem whether it is face-to-face, on the telephone or in writing. Negotiation is not always between two people, it can involve several members from two parties. Children will negotiate among themselves everyday. They will negotiate when they faced with conflict. There are ways in helping children resolve conflict in communication and therefore negotiation plays an important role. The objectives of this paper are to identify the conflict pattern in communication and the use of negotiation skills in resolving conflict in communication among primary school children. A class of 20 subjects from a school in Selangor, Malaysia was chosen to find out the conflict pattern in communication via negotiation skills. The research was carried out for 3 months with the help of the class teacher. It is found that children are able to resolve conflict in communication by the use of negotiation skills.